A memoir of an educational biographer : Gerald Gutek's reflections on the historical and continuing value of a unique craft - Gutek, Gerald Lee (Research in life writing and education, 2024)
"In his interdisciplinary memoir, Gerald Gutek applies history and philosophy of education to educational biography. The author was guided by his focusing goals of exploring his path to becoming an educational biographer and developing working generalizations to his colleagues in the field. Gutek's narrative begins with the author's childhood experiences that inclined him to a career in education, followed by chapters on his doctoral program in the College of Education at the University of Illinois in Champaign-Urbana; his teaching of history and philosophy and education in the School of Education at Loyola University, Chicago; his research and writing of biographies of Johann Heinrich Pestalozzi and Joseph Neef and his textbook, Historical and Philosophical Foundations of Education: a Biographical Introduction; his issues and strategies in writing about Maria Montessori. Throughout the book, Gutek analyzes concepts and applications he developed as an educational biographer such as parallel biographies, slice of life writing, reconsidering overlooked and understudied educators, and the role of place and space in telling life stories"--